Mercados financieros volátiles - Davidson, Paul (2002)
New Keynesians have argued that an ad valorem tax on financial market transactions is socially desirable in thatit will reduce the observed volatility in “super-cfficient financial markets”. Nevertheless, an empirical study appears to conflict with this Keynesian claim: it demonstrates that a reduction in transaction costs is associated with a decline in volatility. This article explains such apparent difference. One”s explanation of the existence of speculative activity depends on whether one accepts or rejects the ergodic axiom. The paper demonstrates that transaction taxes to reduce volatilit does not withstand cither logical or empirical scrutiny. The author suggests the institution of a fixed exchange rate by a governmmental market maker who wil] permit the price to change only at a pre- aumounced rato ar specifio rules. In that sensc, spot financial market price fixity can never produce a free one-way gain option for private sector speculators.